2021
DOI: 10.1186/s12981-021-00391-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of viral suppression among adolescents on antiretroviral treatment in Ehlanzeni district, South Africa: a cross-sectional analysis

Abstract: Background Achieving undetectable viral load is crucial for the reduction of HIV transmissions, AIDS-related illnesses and death. Adolescents (10 to19 years) living with HIV (ALHIV) on antiretroviral treatment (ART) have worse treatment adherence and lower viral suppression rates compared to adults. We report on the clinical factors associated with viral suppression among ALHIV in the Ehlanzeni district, Mpumalanga in South Africa. Methods A cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 24 publications
3
39
0
Order By: Relevance
“…The viral suppression rate of adolescents on ART at the Levai Mbatha CHC was 74.0%, which fell short of the UNAIDS target of 90%. Similar results were reported in Ehlanzeni district, in Mpumalanga province, South Africa (Okonji et al 2021 ), with a viral suppression rate of 74.3%. However, the suppression rate of this study was higher compared to that in Uganda at 65.5% (Natukunda et al 2019 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The viral suppression rate of adolescents on ART at the Levai Mbatha CHC was 74.0%, which fell short of the UNAIDS target of 90%. Similar results were reported in Ehlanzeni district, in Mpumalanga province, South Africa (Okonji et al 2021 ), with a viral suppression rate of 74.3%. However, the suppression rate of this study was higher compared to that in Uganda at 65.5% (Natukunda et al 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…The high number of older adolescents in this study may be influenced by the aging of perinatally infected infants who entered HIV care in childhood and an increasing number of older adolescents seeking care who were probably infected through sexual transmission (Maskew et al 2019 ). Additionally, the high viral suppression rate among adolescents aged 15–19 years could be because they are able to take their ART medication regularly without supervision and possess self-competence on ART adherence (Okonji et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… 3 However, in the Eastern Cape and Mpumalanga, in settings reflecting conditions similar to those reported in the current paper, 71% of adolescents in the Eastern Cape and 74% of those in Mpumalanga were virally suppressed in the past 12 months. 19 , 20 Our study extends the evidence in support of an optimised adolescent HIV care cascade for all South African ALHIV across all healthcare facilities. 21 …”
Section: Discussionsupporting
confidence: 69%
“…The study was conducted in five public primary health care facilities, namely Buffelspruit clinic, Kanyamazane CHC, Cunningmore clinic, Langloop CHC and Naas CHC. Our baseline study in the Ehlanzeni district found a 74% viral suppression rate (confidence interval: 73.1%-74.8%) among ALHIV on antiretroviral treatment in 2019, 12 and retention in care rates at 6, 12, 18 and 24 months of 90.5%, 85.4%, 80.8% and 76.2%, respectively 13 – which fail to meet the UNAIDS target of 95%, 95%, 95% by 2030.…”
Section: Methodsmentioning
confidence: 75%